Effects of specimen size on fatigue life of metallic materials in high‐cycle and very‐high‐cycle fatigue regimes. Issue 6 (24th February 2016) - Sun, C.; Zhang, X.; Liu, X.; Hong, Y.
Abstract: This paper proposes a new method to investigate the effect of specimen size on fatigue life of metallic materials in high‐cycle fatigue and very‐high‐cycle fatigue regimes in the light of statistical analysis. The performance of large specimen is correlated with that of small specimen via control volume (a high stress domain where potential fatigue crack initiation sites are located). The simulation results are in good agreement with a series of experimental data in high‐cycle fatigue and very‐high‐cycle fatigue regimes from literature. The method is helpful for a quantitative estimation of fatigue life of large specimens from the experimental data of small specimens.